2019
DOI: 10.1093/ndt/gfz011
|View full text |Cite
|
Sign up to set email alerts
|

Vascular access in children requiring maintenance haemodialysis: a consensus document by the European Society for Paediatric Nephrology Dialysis Working Group

Abstract: Background There are three principle forms of vascular access available for the treatment of children with end stage kidney disease (ESKD) by haemodialysis: tunnelled catheters placed in a central vein (central venous lines, CVLs), arteriovenous fistulas (AVF), and arteriovenous grafts (AVG) using prosthetic or biological material. Compared with the adult literature, there are few studies in children to provide evidence based guidelines for optimal vascular access type or its management and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 104 publications
0
28
0
Order By: Relevance
“…In a small study of pediatric hemodialysis patients with CVC, alteplase was found to be significantly more effective than heparin in preventing catheter clot formation 22 . Given these results, the European Society for Pediatric Nephrology Dialysis Working Group (ESPNDWG) recommends using tPA as a catheter locking solution to prevent thrombosis 23 . Additionally, fibrin sheath formation may occur in up to 50% of patients with CVC 6 .…”
Section: Modalities Of Long‐term Vascular Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…In a small study of pediatric hemodialysis patients with CVC, alteplase was found to be significantly more effective than heparin in preventing catheter clot formation 22 . Given these results, the European Society for Pediatric Nephrology Dialysis Working Group (ESPNDWG) recommends using tPA as a catheter locking solution to prevent thrombosis 23 . Additionally, fibrin sheath formation may occur in up to 50% of patients with CVC 6 .…”
Section: Modalities Of Long‐term Vascular Accessmentioning
confidence: 99%
“…Without these signs, routine imaging is not recommended. As for thrombus prevention, ESPNDWG recommends using anti‐platelet agents like aspirin, clopidogrel, and ticlopidine within the first few months of AVF creation 34–36 …”
Section: Avf Complicationsmentioning
confidence: 99%
“…Haemodialysis (HD) via a central venous catheter (CVC) for children with kidney failure with replacement therapy (KFRT) remains the commonest form of dialysis in childhood [1]. For young children aged < 2 years, peritoneal dialysis (PD) remains the recommended dialysis access of choice [2], as this modality is associated with fewer complications [1]. If the duration of dialysis is estimated to be 'short-term', for example less than 6 months before a planned kidney transplant, dialysis via a CVC may be adequate to access the vascular system.…”
Section: Introductionmentioning
confidence: 99%
“…However, for longer term HD, consideration should be given to form an arteriovenous fistula (AVF), as long-term HD via a CVC carries significant risks including infection, malfunction, inadequate dialysis, hospitalisation, and central venous stenosis [4]. Despite the known lower complication rates associated with AVF versus CVC [1], European and US databases highlight that the vast majority of children on chronic HD continue to receive dialysis via a CVC [5,6]. Reasons for this may include lack of surgical expertise, clinician preference, and patient and family acceptance of an AVF.…”
Section: Introductionmentioning
confidence: 99%
“…There are three principle forms of vascular access available for the treatment of children with end stage kidney disease (ESKD) by haemodialysis: tunnelled catheters placed in a central vein (central venous lines, CVLs), arteriovenous fistulas (AVF), and arteriovenous grafts (AVG) using prosthetic or biological material. Compared with the adult literature, there are few studies in children to provide evidence based guidelines for optimal vascular access type or its management and outcomes in children with ESKD (Shroff et al, 2019).…”
mentioning
confidence: 99%